Half-mast procession (Palíndromo, 2025)
This visual essay presents the performance Half-Mast Procession, convened by Andrés Valenzuela Arellano on the first anniversary of the social uprising in Chile. Eight photographs document this collective action from October 2020, held on the banks of the Mapocho River following an incident where a teenager was pushed by a police officer. The processional action serves as a ritual of mourning and resistance against state violence, dislocating the Chilean flag, with silent bodies and gestures of dragging and offering. The project combines art, memory, and marika activism, proposing a funerary gesture that questions homeland, justice, and the vulnerable body. It dialogues with the performance At Half-Mast (1988) by the Yeguas del Apocalipsis, during the launch of Carmen Berenguer’s eponymous book, reemerging as a ritual of memory and resistance. Transfeminists and marikas occupied the riverbed as a geographic archive, affirming life among bodies in danger that continue to appear.
Keywords: Mapocho river; political activism; social memory; artistic performance; civil resistance